1984
DOI: 10.1007/bf01989306
|View full text |Cite
|
Sign up to set email alerts
|

The bald-sea-urchin disease: a biopathological approach

Abstract: Individuals of several species of European regular echinoids are affected by a spectacular disease that causes conspicuous lesions on the echinoid body surface. It is a communicable non-specific disease that produces loss of appendages and necrosis of dermal and skeletal tissues. Preliminary investigations indicate that the pathogen is not an alga but could be a bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
1
3

Year Published

1984
1984
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 2 publications
(2 reference statements)
6
62
1
3
Order By: Relevance
“…This finding corresponds with previous studies which have found similar pathogenicity for two other urchin diseases i.e. bald sea urchin disease (Maes & Jangoux 1984, Maes & Jangoux 1985 and deep sea vibrio urchin disease (Bauer & Young 2000), whereby the coelomic fluid of these urchins were also infected by bacteria during disease outbreaks.…”
Section: H Purpurascens (Supplementarysupporting
confidence: 92%
“…This finding corresponds with previous studies which have found similar pathogenicity for two other urchin diseases i.e. bald sea urchin disease (Maes & Jangoux 1984, Maes & Jangoux 1985 and deep sea vibrio urchin disease (Bauer & Young 2000), whereby the coelomic fluid of these urchins were also infected by bacteria during disease outbreaks.…”
Section: H Purpurascens (Supplementarysupporting
confidence: 92%
“…Lesions on Tripneustes gratilla induced by Vexilla vexillum showed several similarities with those of echinoids affected by the bald sea urchin disease described by Maes & Jangoux (1984). In both cases, lesions appeared, which were devoid of epidermis and appendages and displayed a dark green to black colouration.…”
Section: Discussionmentioning
confidence: 51%
“…Such lesions, described by Maes & Jangoux (1984) as the 'bald sea urchin disease', were noted for the first time in California in 1970 (Johnson 1971) and have been recorded since 1978 in the Mediterranean Sea (Höbaus et al 1981). A similar disease, the spotting disease, was also observed in Japanese echinoid hatcheries during summer (Tajima et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…However, some echinoderm mass mortalities have been suggested to be due to microorganisms, e.g. in the asteroid Heliaster kubinjii (Dungan et al, 1982) and several species of echinoids (Johnson, 1971;Pearse et al, 1977;HSbaus et al, 1981;Maes & Jangoux, 1984). These echinoids suffered from a conspicuous condition -the "bald-sea-urchin" disease -that alters the outer surface of the body wall.…”
Section: Diseases Caused By Microorganismsmentioning
confidence: 99%